Voices on birchbark : everyday communication in medieval Russia - Schaeken, J. (Studies in Slavic and general linguistics, 2018)
In Voices on Birchbark Jos Schaeken explores the major role that writing on birchbark - an ephemeral, even 'throw-away' form of correspondence and administration - played in the vibrant medieval merchant city of Novgorod and other cities in the Russian Northwest. Birchbark literacy was crucial to the organization of Novgorodian society; it was integrated into a huge variety of activities and had a broad social basis; it was used extensively by the laity, by women as well as men, by villagers as well as landlords. Voices on Birchbark is the first book-length study of this unique corpus in English. By examining a representative selection of birchbark texts, Jos Schaeken presents fascinating vignettes of daily medieval life and a holistic picture of the pragmatics of communication in pre-modern societies.